Identification and characterization of EGF receptor in individual exosomes by fluorescence-activated vesicle sorting. Issue 1 (1st January 2016) - Higginbotham, James N.; Zhang, Qin; Jeppesen, Dennis K.; Scott, Andrew M.; Manning, H. Charles; Ochieng, Josiah; Franklin, Jeffrey L.; Coffey, Robert J.
Abstract : Exosomes are small, 40–130 nm secreted extracellular vesicles that recently have become the subject of intense focus as agents of intercellular communication, disease biomarkers and potential vehicles for drug delivery. It is currently unknown whether a cell produces different populations of exosomes with distinct cargo and separable functions. To address this question, high-resolution methods are needed. Using a commercial flow cytometer and directly labelled fluorescent antibodies, we show the feasibility of using fluorescence-activated vesicle sorting( FAVS) to analyse and sort individual exosomes isolated by sequential ultracentrifugation from the conditioned medium of DiFi cells, a human colorectal cancer cell line. EGFR and the exosomal marker, CD9, were detected on individual DiFi exosomes by FAVS; moreover, both markers were identified by high-resolution stochastic optical reconstruction microscopy on individual, approximately 100 nm vesicles from flow-sorted EGFR/CD9 double-positive exosomes. We present evidence that the activation state of EGFR can be assessed in DiFi-derived exosomes using a monoclonal antibody (mAb) that recognizes "conformationally active" EGFR (mAb 806). Using human antigen-specific antibodies, FAVS was able to detect human EGFR and CD9 on exosomes isolated from the plasma of athymic nude mice bearing DiFi tumour xenografts. Multicolour FAVS was used to simultaneously identify CD9, EGFR and an EGFR ligand, amphiregulin (AREG), on human plasma-derived exosomes from 3 normal individuals. These studies demonstrate the feasibility of FAVS to both analyse and sort individual exosomes based on specific cell-surface markers. We propose that FAVS may be a useful tool to monitor EGFR and AREG in circulating exosomes from individuals with colorectal cancer and possibly other solid tumours.